Design study of hybrid excitation flux switching motor for electric vehicles - Said, Salmiza (2014)
Hybrid excitation flux switching motor (HEFSM) is an attractive features compared to interior permanent magnet synchronous motor (IPMSM). The hybrid excitation is applied in this project to gain the high torque of the system. This is because the flux was achieved from both permanent magnet and field excitation coil. The design of 6 slot 7 pole inner rotor hybrid excitation motor is analyse by using the JMAG Designer Software which is a simulation software that easily utilized by the user. The analysis of no load, with load and improvement of the motor design is done. The objective of the project of obtaining 207 Nm torque of the motor is succesful since the improvement of the design give the torque of 228.70 Nm at speed 9161r/min from the initial torque of 171.04 Nm at speed 12580r/min. The performance of motor is also improved when the maximum power is increase from 155kW to 173kW. The characteristic represent the high torque, low speed motor performance. An improved design is to gain a better performance in its maximum torque and power production. As the design results, the improved motor enables to keep the better power density in the initial design.